A global soil moisture product at 1 km resolution based on Sentinel-1 (2023-2024) - Fan, Dong; Zhao, Tianjie; Jiang, Xiaoguang; García-García, Almudena; Schmidt, Toni; Samaniego, Luis; Attinger, Sabine; Wu, Hua; Jiang, Yazhen; Shi, Jiancheng; Fan, Lei; Tang, Bohui; et al. (PANGAEA, 2025)
Although soil moisture represents only a small fraction of the Earth's total water content, it plays a pivotal role in the land surface water and energy cycle by regulating key processes such as evaporation, infiltration, and vegetation growth. Remote sensing has become an essential tool for acquiring global-scale soil moisture data. In this study, a dual-polarization algorithm (DPA) is proposed, utilizing VV and VH polarization observations from the Sentinel-1 C-band synthetic aperture radar to produce a global soil moisture dataset at a spatial resolution of 1 km. Due to the observation configuration of Sentinel-1, the dataset exhibits higher temporal resolution in Europe and high-latitude regions than in other continents and lower-latitude areas. The dataset is provided in raster format, with daily ascending and descending observations. To ensure data quality, regions unsuitable for soil moisture retrieval—such as open water, permanent wetlands, frozen ground, snow- and ice-covered surfaces, and urban or built-up areas-have been excluded. User feedback and collaborative efforts to enhance the dataset are welcome.
Keywords: 1km spatial resolution; global; SAR; Sentinel-1; Soil Moisture; water content